2013
DOI: 10.1002/mus.23891
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of QSART to the diagnosis of small fiber neuropathy

Abstract: Assessment of both somatic and peripheral autonomic small nerve fibers enhances diagnostic criteria for SFN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 34 publications
0
65
0
3
Order By: Relevance
“…Patients with SFN have normal routine electrophysiological studies, such that confirmation of the diagnosis relies on an abnormality of small fiber measures including intraepidermal fiber density (IENFD) by skin biopsy, quantitative sensory testing (QST) or sudomotor function by quantitative sudomotor axon reflex test (QSART). In our previous study, addition of QSART to a combination of clinical examination, QST and IENFD increased the diagnostic yield of tests for SFN [1]. This study suggested that somatic sensory and QSART evaluations were additive in the assessment of distal SFN, leading to the hypothesis that sensory and autonomic small fiber dysfunctions occur independently and are not highly correlated in the setting of SFN.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Patients with SFN have normal routine electrophysiological studies, such that confirmation of the diagnosis relies on an abnormality of small fiber measures including intraepidermal fiber density (IENFD) by skin biopsy, quantitative sensory testing (QST) or sudomotor function by quantitative sudomotor axon reflex test (QSART). In our previous study, addition of QSART to a combination of clinical examination, QST and IENFD increased the diagnostic yield of tests for SFN [1]. This study suggested that somatic sensory and QSART evaluations were additive in the assessment of distal SFN, leading to the hypothesis that sensory and autonomic small fiber dysfunctions occur independently and are not highly correlated in the setting of SFN.…”
Section: Introductionmentioning
confidence: 80%
“…Those patients who presented with distal sensory symptoms of pain, without muscle weakness or upper motor neuron signs and had normal nerve conduction studies and electromyography (NCS/EMG), underwent ARS (QSART, cardiovagal and adrenergic testing) with calculation of a composite autonomic severity score (CASS), QST and skin biopsy (IENFD) to assess for SFN. The protocols and procedures employed for the clinical evaluation, electrophysiological studies, QSART, QST and IENFD analysis have been previously described in a study that involved a subset of the current cohort and addressed the contribution of QSART toward diagnostic criteria for SFN [1]. For cooling and vibration thresholds, abnormality was defined as a threshold above the 95th percentile for age, height, weight and gender [1].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sudomotor function tests provide information on peripheral autonomic function. In specialist centers, they are currently used as adjuvant or screening tests for DSPN [73]. The quantitative sudomotor axon reflex test (QSART) [74][75] and the commercially available Q-Sweat [76] have been in clinical application for more than a decade.…”
Section: Methods For Assessment Of Small Fiber Neuropathymentioning
confidence: 99%